2006
DOI: 10.1007/s10620-005-9025-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HCV Genotypes in Patients with End-Stage Renal Disease According to Type of Dialysis Treatment

Abstract: The objective of this study was to investigate the effects of types of dialysis treatments on hepatitis C virus infection and the epidemiologic properties of hepatitis C virus (HCV) infection at three Baskent University hospitals, in Ankara, Adana, and Izmir, Turkey, in 655, 326, and 118 patients with end-stage renal disease, respectively. One hundred thirty patients with HCV viremia among 271 patients with end-stage renal disease seropositive for HCV were included in this cross-sectional study. HCV RNA-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 51 publications
1
22
0
2
Order By: Relevance
“…In developed countries, the prevalence of anti-HCV seropositivity among patients on maintenance HD ranges between 5% and 60%. Patients on HD are at high risk for HCV, with frequency of infection several times higher than that in non-uremic patients [1] . The spread of HCV in HD units is declining, but the prevalence of HCV in HD patients remains high [1] .…”
Section: Minireviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…In developed countries, the prevalence of anti-HCV seropositivity among patients on maintenance HD ranges between 5% and 60%. Patients on HD are at high risk for HCV, with frequency of infection several times higher than that in non-uremic patients [1] . The spread of HCV in HD units is declining, but the prevalence of HCV in HD patients remains high [1] .…”
Section: Minireviewsmentioning
confidence: 99%
“…Patients on HD are at high risk for HCV, with frequency of infection several times higher than that in non-uremic patients [1] . The spread of HCV in HD units is declining, but the prevalence of HCV in HD patients remains high [1] . Several observational studies have demonstrated a significant and independent relationship between anti-HCV seropositive status and lower survival rate in patients with end-stage renal disease (ESRD).…”
Section: Minireviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antalya'nın da, dünyada çok ziyaret edilen şehirlerden biri olması ve ayrıca göç alması 29 Bu çalışmada, HCV viral yük değerleri ve cinsiyet dağılımı açısından genotip 1 ve diğer genotiplerle enfekte hastalar arasında anlamlı bir fark saptanmamıştır. Benzer şekilde, kronik HCV enfeksiyonu olan hastalarda HCV genotiplerindeki farklılık ile cinsiyet dağı-lımı ve HCV-RNA düzeyleri arasında ilişki olmadığı daha önce yapılan çalışmalarda da bildirilmiştir 13,18,25,30,31 . Buna karşın çalışmamızda, genotip 1 ile enfekte hastaların yaş ortalaması diğer genotiplerle enfekte hastalara göre yüksek bulunmuştur (p< 0.001).…”
Section: Gereç Ve Yöntemunclassified
“…Japonya'da genotip 1b HCV enfeksiyonlarının %70'den fazlasını oluşturmaktadır (9). Türkiye'de yapılan HCV genotip çalışmalarında HCV infeksiyonlarının yaklaşık %90'ı genotip 1 olarak bulunmuştur, bunların da büyük çoğunluğu tip 1b olup, tip 2, 3 ve 4 HCV infeksiyonlarına da daha az sık-lıkla rastlanmaktadır (10)(11)(12)(13)(14)(15). HCV genomunda çeşitli mutasyonlar görülmekte ve buna bağlı türümsüler (Quasispecies) ortaya çıkmaktadır.…”
Section: Gereç Ve Yöntemunclassified